PERANCANGAN DAN IMPLEMENTASI APLIKASI E-COMMERCEBERBASIS ANDROID PADA TOKO BUNGA MILLEN FLORIST(Studi Kasus : CV Milenia Cipta Sejahtera) - Dina Mukti Wijayanti Mulia, (2020)
ABSTRACT Design and Implementation of Android-Based E-Commerce Applications in Millen Florist (CASE STUDY: CV Milenia Cipta Sejahtera) By Dina Mukti Wijayanti Mulia CV Milenia Cipta Sejahtera is a stand-alone business entity with the status of a commercial company that engages in many business fields, one of which is the Millen Florist flower shop. With the presence of Millen Florist the company will face problems in its marketing field, Millen Florist has a website but only to see products and information about the company, which causes the system to be less efficient and effective in conducting sales transactions. Therefore an android-based e-commerce application is the solution of this problem to help companies in the completion of product orders. By using the web-service web-admin application on the company side to order and manage reservations (server) can be integrated with the ordering application on the android-based customer (client). With the aim of creating it easy for companies to update product information provided to customers and help make it easier for customers to place orders, purchases, online transactions. The method used is the primary data collection method, namely interviews, observation; Explore secondary data, namely Literature study, online search; the second method of system analysis using the method pieces; all three systems development methods use the waterfall method. With the results obtained from an Android-based e-commerce application that is used as a sales or ordering information system at the Bunga Millen Florist store. Keywords: e-commerce, flower shop, web-service, android.